Critical Analysis of Srota: A Literature Review Arpita - Sarkar, Arpita; Maity, Debnarayan (International Research Journal of Ayurveda & Yoga, 2022)
Human body is nothing but a combination or aggregation of innumerable srota, which means minute individual channels. The word srota etymologically derived from the Sanskrit root “sru-srabane” dhatu which means oozing, permeation, filtration, to flow, exudation, to move etc. Sira, dhamani, marga, rasayani, nadi, pantha, sharir chidra, samvrita-asambrita,sthana, aashaya, niketa, sharir dhatu avakasha, lakshya- alakshya – all these words are synonymous to srota. Some of the srota are visible but some are minute so invisible. This srota or internal transport system has been given a place of basic importance in Ayurveda. According to Charak Samhita, in the human body there is no structure which can originate or synthesize, develop, persist and be wasted or atrophied without srota. This srotas continuously transport dhatus for deposition or transformation. Again there are dosha-vaha srotas. Any type of disease occur due to abnormality in srotas and there are some sign and symptoms due to specific type of srotadushti. But still we do not have a clear understanding about srota in perspective of modern medical science. So in this article we tried to find out way for better understanding about srota.